Multiculturalism, gender and human rights: The case of the native community of Shintuya - Del Alcázar Chávez, Martín (2002)
In May 2000, as a commissioner of the Ombudsman's Office, I visited for the first time the native community of Shintuya, in the department of Madre de Dios. This community is made up mostly of indigenous people of the Arambukt ethnic group and is located in the buffer zone of the Manú National Park; From there you can take the boats to enter other more distant communities.